2008
DOI: 10.1016/j.ympev.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of Conus textile, coxI–coxII intergenic sequences and Conoidean evolution

Abstract: The cone snails belong to the superfamily Conoidea, comprising ∼10,000 venomous marine gastropods. We determined the complete mitochondrial DNA sequence of Conus textile. The gene order is identical in Conus textile, Lophiotoma cerithiformis (another Conoidean gastropod), and the neogastropod Ilyanassa obsoleta, (not in the superfamily Conoidea). However, the intergenic interval between the coxI/coxII genes, was much longer in C. textile (165 bp) than in any other previously analyzed gastropod.We used the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 29 publications
2
41
0
1
Order By: Relevance
“…The dataset used for DNA analysis was mostly derived after Simison et al (2006), Bandyopadhyay et al (2007), Modica et al (2009) and , and included 12S and 16S rDNA sequences of 21 additional neogastropod species belonging in 12 families. EMBL accession numbers of the relevant sequences are the following: FM999072Á75, FM99980Á88, FM999103Á106, FM999111Á116, FM999119Á127, FN391982, FN392228, FN392229, DQ284754 and DQ238598.…”
Section: Methodsmentioning
confidence: 99%
“…The dataset used for DNA analysis was mostly derived after Simison et al (2006), Bandyopadhyay et al (2007), Modica et al (2009) and , and included 12S and 16S rDNA sequences of 21 additional neogastropod species belonging in 12 families. EMBL accession numbers of the relevant sequences are the following: FM999072Á75, FM99980Á88, FM999103Á106, FM999111Á116, FM999119Á127, FN391982, FN392228, FN392229, DQ284754 and DQ238598.…”
Section: Methodsmentioning
confidence: 99%
“…Carinastele kristelleae (Marshall, 1988 Oliverio and Mariottini (2001;12SI) and Bandyopadhyay et al (2008;12S(-)). Alternative primers (Koufopanou et al, 1999) were sometimes used to amplify 16S for problematic taxa.…”
Section: Sampling and Identificationmentioning
confidence: 99%
“…This variation may be considered as extremely high if at intra-species level, even though it is lower than that between genera comparisons, 15.8% and 17.4% at levels of genome and protein-coding genes, respectively for comparison between O. hupensis hupensis and T. hortensoni, and 16% and 17.5% between O. hupensis robertsoni and T. hortensis, and even lower than other comparisons (26-30%) for species in different family or order (Bandyopadhyay et al, 2006(Bandyopadhyay et al, , 2008Simison et al, 2006). In consideration of the difference in morphology and distribution (for details see Liu et al, 1981 andDavis et al, 1995), and in mitochondrial genomes as revealed in the present study, the ribbed-shelled O. hupensis hupensis and the smooth-shelled O. hupensis robertsoni may be considered as separate species, rather than sub-species.…”
Section: Discussionmentioning
confidence: 82%